Predyspozycje psychologiczne w pracy trenera - Lipińska-Grobelny, Agnieszka; Domański, Andrzej (Acta Universitatis Lodziensis. Folia Psychologica, 2008)
The general purpose of this research is the description of the psychological predisposition of working as a trainer. The group of 72 individuals, 36 trainers and 36 non-trainers completed the battery of the following questionnaires: Social Competences Questionnaire, Emotional Intelligence Questionnaire, Psychological Gender Questionnaire, NEO-FFI and Generalized Self-Efficacy Scale. The results reveal that being a trainer can be predicted considering neuroticism, conscientiousness, emotional intelligence and general level of social competences.